2007
DOI: 10.1510/icvts.2007.161356
|View full text |Cite
|
Sign up to set email alerts
|

The influence of levosimendan and iloprost on renal ischemia-reperfusion: an experimental study

Abstract: The effects of iloprost on ischemia-reperfusion injury have been studied on the skeletal, muscle, liver, myocardium, kidney, and spinal cord. However, no sufficient data exist about effects of levosimendan on renal ischemia-reperfusion injury. The purpose of this experimental study was to investigate and compare effectiveness of levosimendan and iloprost on renal injury induced by ischemia and reperfusion. Fifty rabbits were divided into five groups. Levosimendan was continuously infused starting half an hour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 14 publications
3
28
0
Order By: Relevance
“…Although, the findings of our study were in accordance with the recent literature [21][22][23][24] , the small sample size and the lack of a comparable inotrope, which could have potentially increased the confounders, prevented us from drawing definitive conclusions. However, we performed a post hoc power analyses baseline and after the infusion creatinine levels in patients with and without worsening renal function.…”
Section: Limitationssupporting
confidence: 86%
“…Although, the findings of our study were in accordance with the recent literature [21][22][23][24] , the small sample size and the lack of a comparable inotrope, which could have potentially increased the confounders, prevented us from drawing definitive conclusions. However, we performed a post hoc power analyses baseline and after the infusion creatinine levels in patients with and without worsening renal function.…”
Section: Limitationssupporting
confidence: 86%
“…For instance, in a clinical series of patients with cardiogenic shock who have been treated with levosimendan a significant reduction of polyuric syndrome after a stable hemodynamic recovery has been achieved (Caimmi et al, 2011a). Moreover, experimental evidence has shown tubular protection exerted by levosimendan against ischemic injuries (Yakut et al, 2008). Hence, levosimendan, in addition to improving myocardial contraction and exerting vasodilation, has been demonstrated to have the potential to protect against I/R damage through a preconditioning-like effect (Kersten et al, 2000;Soeding et al, 2011) and the reduction of inflammatory and oxidative stress profiles (Avgeropoulou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that levosimendan also attenuates I/R injury in the spinal cord, lung, and in the renal tissue (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%